Study the Effect of Hydrolysis Variables on the Production of Soya Proteins Hydrolysis - AL-Bahri, Mohammed B.; AL-Naimi, Safa A.; Ahammed, Sundus H. (Al-Khwarizmi Engineering Journal, 2019)
This study was conducted to determine the effects of concentration of hydrochloric acids, temperature, and time on the hydrolysis of soya proteins (defatted soya flour) by determining the value of total protein nitrogen concentration, and amino nitrogen concentration of protein, peptides, and amino acids, and then calculated the hydrolysis rate of proteins. The variables of the conditions of hydrolysis process was achieved in this study with the following range value of tests parameter: Concentration of HCl solution ranged between 1-7 N, Hydrolysis temperature ranged between 35-95 °C, and The time of hydrolysis period ranged between 0.5-24 hr. Experiments were designed according to the central composite rotatable design. The practical study has shown the possibility of decreasing the negative effect of the acid on the biological characteristics of the protein; then affecting the possibility of using the product for biological purposes (for medical and microbiological laboratories) by: Decreasing the acid concentration used in the process of hydrolysis, firstly, and Decreasing the temperature of the hydrolysis process, secondly, and then Increasing the period of the time of hydrolysis process, thirdly.